COVID-19 and job stress / Rosliza Md Zani and Shuhaimi Samanol - Md Zani, Rosliza; Samanol, Shuhaimi (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Stress refers to an individual's reaction to different situations. This includes changes in their physiology or psychology in dealing with events in the external environment that are valued more than they can bear, thus affecting their physical and mental well-being. Stress in the workplace is considered a process of interaction between individuals and the work environment, which represents the accumulation of negative emotions produced by work (Kuo et al., 2020).